Discipline in the global economy? : international finance and the end of liberalism - Vestergaard, Jakob (New York : Routledge, 2009)
The book analyzes the IFA as a system of disciplinary power and also gives a comparative analysis of narratives on the Asian crisis and the analysis of liberalism and neoliberalism that serves the double purpose of problematizing the current regime of international economic governance and informing the efforts to outline international financial regulations.
Includes bibliographical references (p. [263]-278) and index.
rpm14/05/13
Loans
Keywords: Financial crises -- Asia; Monetary policy -- Asia; International Monetary Fund; International finance